Stability boundaries of chatter vibrations in turning - Pušenjak, Rudolf (Anali PAZU, 2022)
The paper treats a model of self-excited vibrations in the turning process with one degree of freedom by applying the control structure, which consists of the forward branch, primary feedback and the regenerative feedback. The dynamics of cutting process and the structural dynamics are modeled in the forward branch of the control structure. The time delay, which is an inherent phenomenon of the cutting process and occurs due to the workpiece revolutions is modeled in the regenerative feedback. Vibrations in turning emanate, when the control structure becomes unstable and adversely affect the quality of the cutting process with rough surface and poor dimension accuracy. Vibrations can cause a rapid deterioration of the cutting tool and the possible damage of the lathe. In the paper, the governing delayed differential equation of vibrations in turning process is derived, which is solved by the novel incremental harmonic balance method (IHB method). By means of the proposed method, the stability chart of the turning process is constructed, which in stable areas ensures optimal conditions of turning at variable spindle speed.